1985
DOI: 10.1002/aic.690310615
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of gaseous hydrocarbons on activated carbon: Characteristic kinetic curve

Abstract: The internal diffusion coefficients, Di, of pure methane, ethane and ethylene as well as some of their binary and ternary mixtures, have been calculated at 20°C for solid particles of a commercial activated carbon. It has been observed that the contribution of the surface migration mechanism to the global mass transfer process inside the adsorbent particles can be as much as 7040%. Values for the surface migration coefficient Ds have also been calculated from the relation Di = Dg + KD,, where K is a dimensionl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
45
1

Year Published

1986
1986
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(53 citation statements)
references
References 24 publications
7
45
1
Order By: Relevance
“…1 1 are 7.5 x lo-* and 9.1 x m2/s, respectively. Costa et al (1985) reported the internal diffusion coefficient of ethane on AC-40 activated carbon to be 1.0 x m'/s a t 2OoC, which compares well with the value calculated here.…”
Section: Rpsupporting
confidence: 86%
See 2 more Smart Citations
“…1 1 are 7.5 x lo-* and 9.1 x m2/s, respectively. Costa et al (1985) reported the internal diffusion coefficient of ethane on AC-40 activated carbon to be 1.0 x m'/s a t 2OoC, which compares well with the value calculated here.…”
Section: Rpsupporting
confidence: 86%
“…where The gas-phase concentration profile within the particle is assumed to be parabolic (Tsai et al, 1983): The surface tortuosity factor T, is often assumed equal to rp in the absence of a better approximation (Satterfield, 1981). and 1.5 x m'/s for the surface diffusivities of ethane and propane, respectively, on silica gel a t 323 K. Costa et al (1985) reported an average value of 3.8 x lo-'' m'/s for ethane on AC- …”
Section: Rpmentioning
confidence: 97%
See 1 more Smart Citation
“…It has been successfully applied to describe time-dependent sorption processes in materials, including soil [19,20], minerals [21] activated carbon [22] and waste materials e.g. 'bottom ash' and de-oiled soya [23].…”
Section: Spherical Diffusion Modelmentioning
confidence: 99%
“…Although in the earlier works [1,4] , it was found that diffusion contributed little to breakthrough in adsorption from the gas phase, this can no longer be assumed for adsorption from liquids. Indeed, a large literature discusses the importance of diffusion in the latter system [5,8] . Diffusion through a boundary layer on the outer surfaces of the activated carbon particles may also contribute to the mass transfer resistance.…”
Section: Introductionmentioning
confidence: 99%